The biochemical monitor of physical state before competition in excellent Chinese female rowers - Jin, Z.; Xuexin, L.; Qinian, Z.; Junjie, P.; Yumin, Z. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The purpose of this study was to explore the biochemical monitor of physical state before competition in excellent Chinese female rowers. 10 normal weight athletes and 6 lightweight athletes served as subjects. They were all national class masters, and got 2 gold medals and 2 silver medals at 8th national games. The subjects accomplished four times (one every Sunday) simulate match of 2000M on water, and the serum creatine kinase (CK). Blood urea nitrogen (BUN)(pre-exercise, after-exercise and second dawn) were tested. In addition, the subjects completed the endure-lactate training and the blood lactic acid (LA) was tested after training. Result: Along with the competition date arriving, the rising extent of CK and BUN after-exercise lessened (the two groups of rowers were separately from 83.35 to 27.23 and 47.55 to 33.50 in CK, from 2.66 to 0.38 and from 0.66 to 0.42 in BUN), and the recovery value of CK and BUN in second down also descended(the two groups of rowers were separately from 169.10± 33.67 to 157.75± 33.97 and from 169.0± 44.84 to 147.50± 32.54 in CK, from 7.06± 0.92 to 6.96± 1.61 in normal weight rowers in BUN). So, we thank their performance had lifted. At the same time, through the endure-lactate training, the LA lifted obviously (the two groups of rowers were differently from 12.96± 3.96 to 16.46± 1.63, P<0.01, and from 9.83± 0.76 to 18.33± 0.59, P<0.001). It suggested that the ability of endure-lactate had elevated.